Konstruksi Sosial Nyelasé Di Makam Syaikhona Kholil Bangkalan - Mahsun, Mahsun; Muniri, Muniri (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2018)
The tradition of nyelasé to some cemeteries of the guardiants is a potrait of religious practice which is present and up to now indeed sustainable, for some muslims. In particularly, for muslim community of Bangkalan city. The tradition of nyalse’ to the cemetery of the guardian, such as in cemetery tradition nyelasé of Syaikhona Kholil Bangkalan. As far as we know, the tomb complex of was very crowded by pilgrims from various places, particularly such as: Muslims Madurese, Javanese, and outside Java. Behavior of nyelasé is forming through several processes for the performer, derived from accumulated beliefs from a historic cognitive level. Thus, the behavior of nyelasé to the cemetery of Syaikhona Kholil is a form of behavior that has various motives that has been developing in society. For reveling the motive of the pilgrims, this research is designed as qualitative research by using Belger’s phenomenology approach, those are using objectification, subjectivization, and internalization. By this approach, it is hoped to comprehend the influence of the invironment on the individual awareness as the reality of abjectification, the awareness of individual comprehending of nyelasé as the Sub-certification and internalization as the synthesis of environmental influences and individual awareness. Thus, it will be able to create an independent religious practice.